THE EFFECTIVENESS OF MATH GAMES LEARNING MEDIA ON MATHEMATICS LEARNING OUTCOMES OF FOURTH GRADE STUDENTS AT SD LABSCHOOL UNNES - Sabrina Erlita; Elok Fariha Sari (JME (Journal of Mathematics Education), 2026)
The use of digital-based learning media in elementary mathematics instruction has not been optimally implemented, which contributes to low student engagement and learning outcomes. This study aimed to examine the effectiveness of Math Games learning media in improving the mathematics learning outcomes of fourth-grade students at SD Labschool UNNES. The study employed a quantitative approach using a quasi-experimental design with a nonequivalent control group. The research subjects consisted of 38 fourth-grade students, with 19 students in the experimental group and 19 students in the control group. The experimental group received instruction using Math Games, while the control group was taught using conventional learning media. Data were collected through pretest and posttest instruments and analyzed using nonparametric statistical tests. The results indicated that students in the experimental group demonstrated a greater improvement in mathematics learning outcomes compared to those in the control group. Statistical analysis revealed a significant difference in learning outcomes between the two groups. These findings suggest that the implementation of Math Games learning media is effective in enhancing elementary students’ mathematics learning outcomes and can serve as an innovative alternative for mathematics instruction in elementary schools.